Measuring membrane capacitance during a depolarizing stimulus - Chen, Peng. (2010)
Regulated by the combined actions of various proteins and lipids, exocytosis in neurons or neuroendocrine cells is a highly dynamic process. It involves the transition of secretory vesicles through distinct molecular states in a time scale of seconds and final rapid Ca dependent vesicle fusion in a time scale of milliseconds. It is critical to resolve the highly dynamic kinetic steps along the molecular cascade of exocytosis in order to pin down the specific actions of regulatory molecules and eventually decipher this complex and fundamental process.